If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -1(y + 4) = -20 Reorder the terms: 4y + -1(4 + y) = -20 4y + (4 * -1 + y * -1) = -20 4y + (-4 + -1y) = -20 Reorder the terms: -4 + 4y + -1y = -20 Combine like terms: 4y + -1y = 3y -4 + 3y = -20 Solving -4 + 3y = -20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3y = -20 + 4 Combine like terms: -4 + 4 = 0 0 + 3y = -20 + 4 3y = -20 + 4 Combine like terms: -20 + 4 = -16 3y = -16 Divide each side by '3'. y = -5.333333333 Simplifying y = -5.333333333
| 2x+4x=5x-7 | | A=2h^2-4 | | 49s^2+42s=9 | | 10(x+5)=10 | | 4g+3(-7+5g)=1-g | | 12=7n | | 15x-4=40x+1 | | 2x+5=-5x+75 | | 7ab+6b=5c | | 15u^2-28u+5=0 | | -m(3)=7-9 | | 4x-6y+2z-5x-3y+8z= | | 12(13x+4)=-1824 | | y=20+5n | | 10k^2=20k | | 2(x+7)+3=-1+4(x+7) | | -3x+1=7-x | | 40+8.50x+16.25x=40+9.50+15.25x | | 6p^3+7p^3= | | 5=13+15x-21 | | 2(3p-8)-3(p-7)-19p= | | y^2-9y-14=0 | | 3m-13=26 | | 5x-8=7x-8-2x | | 3a+c=5b-7a | | 2=10y+6 | | 25=r-12 | | y^2=9y-14 | | 19x+33=2x^2 | | q+18.30=20 | | 5(t-3)-2x=-30 | | a+(-10)=0 |